Gens una sumus – we all are a one whole family: a sociological analysis of ethnogenesis of Belarusians - Shavel, Sergey A. (Journal of the Belarusian State University. Sociology, 2020)
The article explains through sociological analysis how Belarusian ethnic group was emerged and was transformed into Belarusian people as well as forming Belarusian sovereign national state. Such things as multiethnic identity and consolidation of the Belarusian people are considered in the context of historical memory.
Keywords: ethnos; ethnogenesis; identity; ethnocracy; multi-ethnicity; people; historical memory